Positive allosteric adenosine A2A receptor modulation suppresses insomnia associated with mania- and schizophrenia-like behaviors in mice - Lin, Yang; Roy, Koustav; Ioka, Shuji; Otani, Rintaro; Amezawa, Mao; Ishikawa, Yukiko; Cherasse, Yoan; Kaushik, Mahesh K.; Klewe-Nebenius, Daniela; Zhou, Li; Yanagisawa, Masashi; Oishi, Yo; et al. (Frontiers in Pharmacology, 2023)
Background: Insomnia is associated with psychiatric illnesses such as bipolar disorder or schizophrenia. Treating insomnia improves psychotic symptoms severity, quality of life, and functional outcomes. Patients with psychiatric disorders are often dissatisfied with the available therapeutic options for their insomnia. In contrast, positive allosteric modulation of adenosine A2A receptors (A2ARs) leads to slow-wave sleep without cardiovascular side effects in contrast to A2AR agonists. Methods: We investigated the hypnotic effects of A2AR positive allosteric modulators (A2AR PAMs) in mice with mania-like behavior produced by ablating GABAergic neurons in the ventral medial midbrain/pons area and in a mouse model of schizophrenia by knocking out of microtubule-associated protein 6. We also compared the properties of sleep induced by A2AR PAMs in mice with mania-like behavior with those induced by DORA-22, a dual orexin receptor antagonist that improves sleep in pre-clinical models, and the benzodiazepine diazepam. Results: A2AR PAMs suppress insomnia associated with mania- or schizophrenia-like behaviors in mice. A2AR PAM-mediated suppression of insomnia in mice with mania-like behavior was similar to that mediated by DORA-22, and, unlike diazepam, did not result in abnormal sleep. Conclusion: A2AR allosteric modulation may represent a new therapeutic avenue for sleep disruption associated with bipolar disorder or psychosis.